Ewing sarcoma of the adrenal gland: a case report and review of the literature - Eddaoualline, Hanane (J Med Case Rep, 2018)
BACKGROUND: Ewing sarcoma/primitive neuroectodermal tumor is a family of highly malignant proliferation of neuroectodermal origin, most often skeletal, adrenal localization is extremely rare. Only few cases have been reported in the literature. Classical management includes radical surgery with adjuvant chemotherapy or radiotherapy or both. This case report is the only one where recurrence was surgically removed, and it confirms the importance of adjuvant treatment, and the efficacy of neoadjuvant chemotherapy. CASE PRESENTATION: We report the case of a 23-year-old Moroccan woman presenting with flank pain. An abdominal computed tomography scan showed a large and enhancing left suprarenal mass. After radical nephrectomy, histologic examination revealed a small round cell proliferation. The diagnosis of Ewing sarcoma was confirmed by molecular analysis; time to final diagnosis was 5 months due to financial and coordination issues. Computed tomography (on an asymptomatic patient) revealed a locoregional recurrence, our patient received 12 cycles of the vincristine, doxorubicin and cyclophosphamide/ifosfamide and etoposide protocol used in an alternating schedule, with partial radiologic response (62%) and pathologic complete response, then underwent adjuvant radiotherapy of 45 Gy. The young women is still in remission after 36 months of follow-up. CONCLUSIONS: Our patient had an early recurrence due to absence of adjuvant treatment, but did respond well to neoadjuvant chemotherapy with a pathologic complete response. Management of adrenal Ewing sarcoma could be extrapolated from skeletal one with good outcomes even in locoregional recurrence.